Abnormal vitamin D and lipid profile in HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients - Derakhshan, Reza; Mirhosseini, Ali; Ahmadi Ghezeldasht, Sanaz; Jahantigh, Hamid Reza; Mohareri, Mehran; Boostani, Reza; Derakhshan, Mohammad; Rezaee, Seyed Abdolrahim (Molecular biology reports, 2020)
The HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurodegenerative disease of host-HTLV-1 interactions. In many virus-associated diseases and multiple sclerosis, the importance of vitamin-D and lipid profile has been demonstrated, thus similarly, their impacts were evaluated in HAM/TSP patients, in this study. Vitamin D and lipid profile were assessed in 120 healthy subjects (HSs), along with a proviral load (PVL) in 91 HAM/TSPs and 169 HTLV-1 carriers (ACs). The mean level of triglyceride and LDL in the HAM/TSPs were higher than HSs ( P = 0.008 and 0.008, respectively), but no significant difference has been found between ACs and HSs. However, the level of HDL and vitamin-D in the HAM/TSP subjects were lower than HSs ( P = 0.01 and P = 0.006, respectively). In HTLV-1 infected subjects, PVL was statistically associated with cholesterol (R = 0.24, P = 0.038), triglycerides (R = 0.26, P = 0.01) and HDL (R = 0.28, P = 0.001), and in HAM/TSPs there was a strong association between the severity of the disease, as determined by the OMDS and cholesterol ( P = 0.01). Furthermore, in the HAM/TSPs, positive correlations between vitamin-D and age (R = 0.23, P = 0.028) and triglycerides (R = 0.38, P = 0.001) were found, also a significant correlation between PVL and LDL (R = 0.21, P = 0.001) and a weak correlation between PVL and OMDS (R = 0.4, P = 0.07) were noted. However, there was no correlation between PVL and urinary disturbance. Furthermore, PVL range of more than 600 copies/10 4 lymphocytes had a strong correlation with OMDS ( P = 0.05), but not with urinary disturbance. It’s more likely that HAM/TSP patients have an imbalanced lipid profile and low levels of vitamin D and may represent a potentially useful target for intervention in HTLV-1 associated diseases.